Myocardial Salvaging Effect of Metformin In Isoproterenol Induced Myocardial Injury in Rats - Sultana, Nadia; Shahriar, Iram; Iqbal, Md Jalal Uddin; Rowshan, Mahfuza Mazeda; Haque, Sumona; Israt, Ummey Honey; Khatun, Ayasha (Sir Salimullah Medical College Journal, 2022)
Background: Cardiovascular disease is one of the most common causes of death. Various clinical and experimental investigations demonstrate that metformin, a widely used antidiabetic drug, exhibits cardioprotective properties against myocardial infarction. The present study was designed to observe the cardioprotective effect of metformin, in isoproterenol induced myocardial injury in rats. Methods and Materials: A total number of 35 rats were taken for the experiment. Wistar Albino rats of either sex, were divided into 5 groups (n=7). After grouping, two groups Group III and Group V were induced diabetes by administration of single dose of Alloxan Monohydrate 120mg/kg body weight intraperitoneally. Group IV and V received metformin 100mg/kg/day for 4 weeks (2nd week – 5th week) and then isoproterenol 85mg/kg/day was given intraperitoneally 24 to 48 hour prior to scarifice (1st and 2nd day of 6th week). Biochemical parameters LDH and troponin I levels were estimated. Histopathological examination of heart was also done. Results: Results showed, mean LDH, Troponin-I levels of Isoproterenol treated diabetic group G-III were 913.71±24.2, 2.19±0.07. The levels were 498.57±15.1, 1.13±0.08, in G-V. Mean LDH, Troponin-I levels were 793.71±70.4, 1.36±0.05 G–II and levels were 411.57±21.9, 0.16±0.05 in G-IV. P (<0.05) value indicates there is significant difference between G III vs G V and G II vs G IV. Microscopic examination of heart showed myocardial structure disorganization, necrosis, edema scoring “3-4” in isoproterenol treated group G II and G III. In G IV and G V microscopic examination showed reduction of necrosis and edema, nearly normal cardiac architecture scoring “0-1. Conclusion: Study results showed that metformin has cardioprotective effect in isoproterenol induced myocardial injury. Sir Salimullah Med Coll J 2021; 29(2): 158-165